2019
DOI: 10.1186/s12909-019-1454-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving clinical judgment by simulation: a randomized trial and validation of the Lasater clinical judgment rubric in Chinese

Abstract: BackgroundThe development and assessment of clinical judgment ability are essential in nursing education. The Lasater Clinical Judgment Rubric (LCJR) was shown to be valid in evaluating nursing students’ learning outcomes and skills in western cultures but has not been validated in mainland China. This study aimed to compare a simulation-teaching model with a traditional teaching method in enhancing the clinical judgment ability of nursing undergraduate students and to validate the Chinese version of the Lasat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 39 publications
3
40
1
1
Order By: Relevance
“…A previous systematic review reported that problem-based learning could improve nurses’ integrative thinking and reflection processes by providing comprehensive clinical situations [ 50 ]. Additionally, nursing curriculums that included simulations and provided realistic situations helped improve students’ nursing procedures, communication skills, empathy, clinical judgment, and self-efficacy [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review reported that problem-based learning could improve nurses’ integrative thinking and reflection processes by providing comprehensive clinical situations [ 50 ]. Additionally, nursing curriculums that included simulations and provided realistic situations helped improve students’ nursing procedures, communication skills, empathy, clinical judgment, and self-efficacy [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it allows the participant to apply the theoretical content taught in the classroom and develop necessary skills for professionals in clinical practice. 15 Positive and negative aspects of clinical simulation Rosa MEC, Pereira-Ávila FMV, Góes FGB, Pereira-Caldeira NMV, Sousa LRM, Goulart MCL Theoretical teaching, associated with simulation, promotes the development of critical thinking in nursing students. If they are directed to practical teaching in clinical settings, it can cause considerable damage to health and even concern patients because they do not have enough skills to act in care.…”
Section: Discussionmentioning
confidence: 99%
“…The sum score distinguishes four phases of clinical judgment: beginning (11 points), developing (12–22 points), accomplished (23–33 points), and exemplary (34–44 points) (Georg et al, 2019). The Chinese version of the LCJR reported high factor loadings and reliabilities and no bias from age, gender, or raters (Yang et al, 2019). In this study, the Cronbach's alpha coefficient was 0.902.…”
Section: Methodsmentioning
confidence: 99%